O sistema de planejamento estratégico do Exército Brasileiro (SIPLEx) : uma análise da doutrina militar terrestre do Exército Brasileiro e do seu planejamento (2002- 2007) - Silva, Carlos Eduardo de Melo Viegas da (2009)
The object of this work is the land strategy of the Brazilian Army. It´s study is carried out by means of an analysis of the SIPLEx, which is the Brazilian Army Planning System, in use since 1985. As the purpose of an army´s planning system is the production of military power, the basics components that may generate this kind of power are discussed, among them the major the importance of military efficiency The Brazilian land strategy is detailed in terms of its doctrines. Are examined more closely the Alfa Doctrine (GLO Guarantee of the Law and the Order) and the Gama Doctrine (Amazon defense). It is discussed in what extent the Alfa Doctrine (GLO) represents a rupture with the strategicals concepts the Brazilian Army used to put in practice during the Cold War and it is also discussed the role of the guerrilla tactics in the Amazon defense.